2024
DOI: 10.1002/bse.3702
|View full text |Cite
|
Sign up to set email alerts
|

Circular supply chains in manufacturing—Quo vadis? Accomplishments, challenges and future opportunities

Arijit Bhattacharya,
Shefali Srivastava,
Abhijit Majumdar

Abstract: Circular approach in manufacturing supply chain (SC) operations yields multiple benefits through optimal utilisation and consumption of resources. This study maps the scope and structure of circularity in the manufacturing SC discipline and explores the evolution of the domain over time. We review 946 journal articles published between 2013 and September 2023. Our study identifies key drivers and barriers to circular economy (CE) deployment in manufacturing SC operations, bibliometric parameters, emerging rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 241 publications
0
6
0
Order By: Relevance
“…In recent times, innovation in food waste management and sustainability has received much attention from researchers and practitioners. It is identified that CE approach plays a role in the promotion of innovation in enterprises (Bhattacharya et al, 2024). According to Pan et al (2023), data from Chinese listed companies revealed that the adoption of CE practices can stimulate enterprise innovation output.…”
Section: The Solutions Offered By Circular Economymentioning
confidence: 99%
“…In recent times, innovation in food waste management and sustainability has received much attention from researchers and practitioners. It is identified that CE approach plays a role in the promotion of innovation in enterprises (Bhattacharya et al, 2024). According to Pan et al (2023), data from Chinese listed companies revealed that the adoption of CE practices can stimulate enterprise innovation output.…”
Section: The Solutions Offered By Circular Economymentioning
confidence: 99%
“…Organizations are actively seeking novel approaches to reshape their business operations and supply chains, aiming to mitigate negative consequences and enhance value generation for stakeholders. Consequently, the concept of the CE has emerged as a viable alternative, capable of addressing contemporary environmental and social concerns alongside economic progress (Bhattacharya et al, 2024;Sinha, 2022;Tseng et al, 2024).…”
Section: Supply Chain Performancementioning
confidence: 99%
“…Collaboration is essential for overcoming the complexity of implementing circular economy strategies (Bhattacharya et al, 2024). By fostering partnerships and alliances with stakeholders, organizations can pool resources, share knowledge, and develop joint initiatives that address systemic challenges more effectively (Hopkinson et al, 2020;Lahane & Kant, 2021).…”
Section: Asset Managementmentioning
confidence: 99%
See 2 more Smart Citations